2017
DOI: 10.1093/jnci/djx037
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival Prediction and Usefulness of Second-Line Chemotherapy in Advanced Pancreatic Adenocarcinoma

Abstract: This prognostic nomogram and score in patients with aPDAC can accurately predict OS before administration of L2 and may help clinicians in their therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 37 publications
1
47
2
Order By: Relevance
“…Subgroup analysis of the patients in this study showed that a low GPS and a low CEA level were independently associated with a good outcome. Previous reports indicated that the performance status, CA19-9 level, duration of the first-line chemotherapy, and inflammation-based prognostic score were important prognostic factors in a salvage setting [25,26] [29]. It is now widely accepted that the inflammation-based prognostic score, such as the GPS, is a reliable indicator of survival for many types of malignant solid tumors including PC in various settings [11] [30].…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis of the patients in this study showed that a low GPS and a low CEA level were independently associated with a good outcome. Previous reports indicated that the performance status, CA19-9 level, duration of the first-line chemotherapy, and inflammation-based prognostic score were important prognostic factors in a salvage setting [25,26] [29]. It is now widely accepted that the inflammation-based prognostic score, such as the GPS, is a reliable indicator of survival for many types of malignant solid tumors including PC in various settings [11] [30].…”
Section: Discussionmentioning
confidence: 99%
“…Better understanding of BTC prognosis may emerge from molecular studies [21] and also from the development of more informative databases including easily available clinicobiological parameters that were not available in our study, such as smoking status or neutrophil-to-lymphocyte ratio [22,23]. Overall, our results highlight a considerable heterogeneity in survival in patients with aBTC receiving L2, with median OS ranging from 3 to 13 months.…”
Section: Discussionmentioning
confidence: 73%
“…Obstructive jaundice caused by biliary tract invasion is a common complication and a negative prognosticator in pancreatic cancer patients . Early chemotherapy without optimal biliary drainage might increase chemotherapy related toxicity .…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive jaundice caused by biliary tract invasion is a common complication and a negative prognosticator in pancreatic cancer patients. 24 Early chemotherapy without optimal biliary drainage might increase chemotherapy related toxicity. 25,26 Our study showed that patients presenting with obstructive jaundice had an unfavorable outcome if they receive palliative chemotherapy within 2 weeks after cancer F I G U R E 2 Kaplan-Meier curve of overall survival (A) and postchemotherapy survival (B) in patients stratified by different time interval groups diagnosis.…”
Section: Discussionmentioning
confidence: 99%